GC-MS analysis, antimicrobial and antiulcer evaluations of ginger-infused virgin coconut oil - Ibeabuchi Jude Ali; Okorie Ndidiamaka H; Adonu Cyril C; Omeh Romanus C; Obidiegwu Onyeka C; Okonkwo Raymond M; Okafor Judith O; Okoye Festus BC (German Journal of Pharmaceuticals and Biomaterials)
Medicinal herb-infused oil is utilized in folkloric medicine due to its efficacy in ameliorating various diseases of humans; even with this evidence, most herbs are still underutilized and poorly investigated. This prompted the investigation of ginger-infused virgin coconut oil's chemical composition and antimicrobial and antiulcer activities (GIVCO). The virgin coconut oil was produced using the natural fermentation method. Dried ginger and VCO (1:10) were infused for three days and then filtered to obtain ginger-infused virgin coconut oil. GC-MS was used to detect GIVCO chemical constituents. The agar well diffusion method was used for antimicrobial evaluation test organisms. The ethanol and indomethacin-induced ulcer models were used for antiulcer evaluation. The GC-MS analysis identified the presence of lauric acid methyl ester, Myristic acid, Palmitic Acid, Oleic acid, Capric acid, Stearic acid, Caryophyllene, Docosahexaenoic Acid methyl ester. At 100 mg/ml, inhibition zone diameter (IZD) ranged from 10-16 mm for various strains of bacteria and 10-21 mm for various strains of fungi. The effect of GIVCO on tested organisms compared favorably to that of standard drugs. The acute toxicity study of GIVCO is atoxic. The antiulcer activity demonstrated a dose-dependent effect; at 100 mg/ml, the GIVCO protected the intestine with a %UI of 80 and 63 for ethanol and indomethacin model against the standard omeprazole with 50% UI. The study demonstrated the potential of GIVCO as an alternative medicine against antimicrobial infections and the prevention of stomach ulcers.